Assignment China An Oral History of American Journalists in the People's Republic - Chinoy, Mike (Columbia University Press, 2023)
Reporting on China has long been one of the most challenging and crucial of journalistic assignments. Foreign correspondents have confronted war, revolution, isolation, internal upheaval, and onerous government restrictions as well as barriers of language, culture, and politics. Nonetheless, American media coverage of China has profoundly influenced U.S. government policy and shaped public opinion not only domestically but also, given the clout and reach of U.S. news organizations, around the world.This book tells the story of how American journalists have covered China-from the civil war of the 1940s through the COVID-19 pandemic-in their own words. Mike Chinoy assembles a remarkable collection of personal accounts from eminent journalists, including Stanley Karnow, Seymour Topping, Barbara Walters, Dan Rather, Melinda Liu, Nicholas Kristof, Joseph Kahn, Evan Osnos, David Barboza, Amy Qin, and Megha Rajagopalan, among dozens of others. They share behind-the-scenes stories of reporting on historic moments such as Richard Nixon's groundbreaking visit in 1972, China's opening up to the outside world and its emergence as a global superpower, and the crackdowns in Tiananmen Square and Xinjiang. Journalists detail the challenges of covering a complex and secretive society and offer insight into eight decades of tumultuous political, economic, and social change.At a time of crisis in Sino-American relations, understanding the people who have covered China for the American media and how they have done so is crucial to understanding the news. Through the personal accounts of multiple generations of China correspondents, Assignment China provides that understanding